2017
DOI: 10.1002/ange.201706523
|View full text |Cite
|
Sign up to set email alerts
|

Strukturelle und elektronische Flexibilität in Hydriden von Zintl‐Phasen mit Tetrel‐Wasserstoff‐ und Tetrel‐Tetrel‐Bindung

Abstract: Die Hydrierung von Zintl-Phasen ermçglicht die Bildung neuer Strukturmotive mit Hauptgruppenelement-Wasserstoff-Bindungen im Festkçrper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…As the structural properties of the materials under consideration are crucial for the interpretation of their NMR results, we will first review the crystallographic details that are published already elsewhere. [20][21][22][23][24] Within the homologue series of the Zintl phase deuterides AeTtD (1+y) , Ae = Ca-Ba, Tt = Si-Sn, three distinct structure types occur ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As the structural properties of the materials under consideration are crucial for the interpretation of their NMR results, we will first review the crystallographic details that are published already elsewhere. [20][21][22][23][24] Within the homologue series of the Zintl phase deuterides AeTtD (1+y) , Ae = Ca-Ba, Tt = Si-Sn, three distinct structure types occur ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining Tt atoms are bound to deuterium. Furthermore, diffraction showed that the chain-coordinating deuterium site is always under-occupied (details were given elsewhere [22][23][24] ) which is indicated by a correction term x in the chemical formula. The compounds CaSiD 4/3Àx , 20,21…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations